Analysis of Hepatitis B virus (HBV) mutations in patients from Western Saudi Arabia with chronic disease - Sherif Aly El-Kafrawy; Ghazi Abdulatif Jamjoom; Hisham Othman Akbar; Hind Ibrahim Baker Fallatah; Mai Mohamed El-Daly; Yousef Abdulfattah Qari; Abdullah Saeed Alghamdi; Mohamed Babatin; Mohammed Abdullah Alsaedi; Noura Abdulhamid Othman; Tagreed Lafi Al-Subhi; Mohamed Abdel-Hamid; et al. (Journal of Infection in Developing Countries)
Introduction: Extensive research has provided a link between HBV variants and the clinical complications of liver diseases. This study was performed to further investigate the relationship between HBV variants in preS, S and BCP/PC regions and disease progression in chronic hepatitis B (CHB) cases in Jeddah, Saudi Arabia.